2-Chloro-2’Hydroxy-4’-Ethoxychalcone Oxime as an Analytical Reagent for Copper(II) - Desai, J.J.; Desai, P.G.; Mehta, A.G. (Asian Journal of Chemistry, 2010)
2-Chloro-2'-hydroxy-4' -ethoxychalcone oxime (CHECOX) has been prepared and used for the gravimetric and spectrophotometric determination of copper(II) at pH 6.0-6.5. Job's method of continuous variation and Yoe and Jones mole ratio method show metal-ligand ratio in the complex to be 1 : 2. The molar absorptivity of the complex at 400 nm is found to be 1.4912 X 104 L. mole-1 cm-1 . The stability constant determined spectrophotometrically is found to be 2.72 X 106 and Gibb's free energy change for complex formation reaction is calculated to be 8.83 kcal/mole. The Beer's law is obeyed upto 20 ppm of Cu(II) ion at 400 nm.